Pengaruh Model Pembelajaran Snowball Throwing dan Talking Stick Terhadap Hasil Belajar Pendidikan Agama Hindu dan Budi Pekerti Siswa SMK - A.A. Alit Putra Baskara; I Made Wiguna Yasa; I Made Arsa Wiguna (Cetta: Jurnal Ilmu Pendidikan, 2026)
The low learning outcomes in Hindu Religious Education and Character Education indicate the need for learning models that actively engage students in the learning process. This study aimed to analyze the effect of the Snowball Throwing and Talking Stick learning models on the learning outcomes of Grade X students at SMK Prshanti Nilayam. This study employed a quantitative approach using a quasi-experimental design. The sample consisted of 80 students, including 25 students in the Snowball Throwing class, 26 students in the Talking Stick class, and 29 students in the control class. Data were collected through a learning achievement test that had met validity and reliability requirements and were analyzed using descriptive and inferential statistics. The results showed that the mean score of the Snowball Throwing class increased from 60.44 (pretest) to 76.12 (posttest), while the Talking Stick class increased from 60.27 to 75.42. The control class increased from 49.93 to 64.93. One-Way ANOVA revealed a significance value of p < 0.001 (F = 14.457), indicating that the implementation of Snowball Throwing and Talking Stick learning models affected students’ learning outcomes. The LSD post hoc test further showed that both experimental classes achieved higher learning outcomes than the control class. Therefore, Snowball Throwing and Talking Stick can be considered effective alternative learning models for improving learning outcomes in Hindu Religious Education and Character Education.